2013
DOI: 10.1159/000356603
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of Bone Marrow-Derived Cells Prevents Disease Progression in Experimental Silicosis

Abstract: Background/Aims: Bone marrow-derived cells (BMDCs) reduced mechanical and histologic changes in the lung in a murine model of silicosis, but these beneficial effects did not persist in the course of lung injury. We hypothesized that repeated administration of BMDCs may decrease lung inflammation and remodeling thus preventing disease progression. Methods: One hundred and two C57BL/6 mice were randomly divided into SIL (silica, 20 mg intratracheally [IT]) and control (C) groups (saline, IT). C and SIL groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…In the murine model used in the present study, silicosis was induced by a single exposure to crystalline silica, which, after 15 days, led to lung mechanical and histological changes that resembled those of human silicosis (Faffe et al, 2001; Maron-Gutierrez et al, 2011; Lopes-Pacheco et al, 2013). In addition, we have decided to use a C57BL/6 mouse strain, which is a prototypical Th1-type mouse strain.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In the murine model used in the present study, silicosis was induced by a single exposure to crystalline silica, which, after 15 days, led to lung mechanical and histological changes that resembled those of human silicosis (Faffe et al, 2001; Maron-Gutierrez et al, 2011; Lopes-Pacheco et al, 2013). In addition, we have decided to use a C57BL/6 mouse strain, which is a prototypical Th1-type mouse strain.…”
Section: Discussionmentioning
confidence: 88%
“…Mice exposed to silica exhibited higher Est,L and ΔP2,L values, which were associated with the presence of silicotic granulomas, alveolar collapse, thickening of alveolar septa, infiltration of inflammatory cells in lung parenchyma, and collagen fiber deposition. The increase in airway resistive pressure (ΔP1,L) may have been due to the greater number of cells in the bronchi associated with areas of lumen obstruction (Faffe et al, 2001; Borges et al, 2002; Maron-Gutierrez et al, 2011; Lopes-Pacheco et al, 2013; Cruz et al, 2016). Bosutinib decreased both Est,L and ΔP2,L likely due to reduction in alveolar collapse, interstitial edema, thickening of alveolar septa, cell infiltration and collagen fiber content, whereas Δ P 1,L did not change after therapy which may be attributed to the presence of the silica particle adhere to the airway and airway hyperreactivity (Ferreira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, in house dust mite extract (HDM)‐induced allergic asthma, a single dose of MSCs reduced some inflammatory parameters but was unable to ameliorate lung function or remodeling . Some reports have indicated that repeated cell‐based therapy yielded better therapeutic effects, either by preventing disease progression or by further reducing inflammation and remodeling, in experimental silicosis and elastase‐induced emphysema . However, the impact of multiple‐dose cell therapy regimens in experimental allergic asthma remains unknown.…”
Section: Introductionmentioning
confidence: 99%